1986
DOI: 10.1136/bjo.70.12.918
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of visual function after optic neuritis: a comparison of clinical tests.

Abstract: SUMMARY A group of 53 patients who had suffered an attack of unilateral (n=45) or bilateral (n=8) optic neuritis more than six months before were subjected to a battery of tests to determine their spatial contrast sensitivity, visual field, and colour vision. The 106 eyes investigated were classified according to their clinical status and visual acuity at the time of the study into unaffected (n=45), recovered (n=33), and non-recovered (n=28). At least one of the three tests gave an abnormal result in 67%, 88%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…A recent study with comparison of tests [30,31] found no correlation of VEP latency with the other tests but suggested that VEP amplitude did relate to other methods. Amplitude is determined by the number of functioning neurones.…”
Section: Optic Neuritismentioning
confidence: 95%
“…A recent study with comparison of tests [30,31] found no correlation of VEP latency with the other tests but suggested that VEP amplitude did relate to other methods. Amplitude is determined by the number of functioning neurones.…”
Section: Optic Neuritismentioning
confidence: 95%
“…Beck et al (1984), Sanders et al (1986) have reported long back that asymptomatic visual dysfunction may be detected in the fellow eyes of a patient with acute unilateral optic neuritis [1,2]. In ONTT, abnormal visual acuity was seen in 13.8% and abnormal color vision (Ishihara plates) in 20.1% of fellow eyes.…”
Section: Discussionmentioning
confidence: 99%
“…However Sethi et al reported persistently abnormal visual parameters (visual acuity in 10.5%, contrast sensitivity in 26.3%, visual field defect in 21% and color vision in 10.5% of fellow eyes) at 3 months of follow up [3]. In a study by Sanders et al also; reduced contrast sensitivity was seen in 27%, visual field defects in 5% and abnormal color vision in 14% of unaffected eyes after 6 months of treatment of optic neuritis [2]. As evident from these studies, abnormalities in all visual parameters improve, but even after treatment they persist in fellow eyes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most patients have some lasting visual impairment. Even when a patient's visual acuity does return to normal, abnormalities frequently remain in other measures such as contrast sensitivity, color vision, and visual field (Fleishman 1987;Sanders 1986). …”
Section: Description Of the Conditionmentioning
confidence: 99%